The Effectiveness of Avocado Leaf Ethanol Extract Ointment (Persea americana Mill.) on Incision Wound Healing in White Mice - Sidoretno, Wahyu Margi; Putriani, Kony; Haikal, Fikri (JURNAL PROTEKSI KESEHATAN, 2025)
Avocado leaves (Persea americana Mill.) contain bioactive compounds that can aid in the wound healing process by reducing the number of neutrophils. This study aims to determine the effect of avocado leaf ethanol extract ointment on healing cuts on the back skin of white mice (Mus musculus ) strain Balbc. The study was based on a laboratory experimental design with a post-test control group. The research subjects included 5 male white mice for each treatment group. The treatment groups used extract concentrations in ointment preparations of K15%, K35%, and K45%, with a negative control (Vaseline) and a positive control (Gentamicin). The cuts were made by injuring the back skin along a length of 15 mm and a depth of 2 mm. Observations of wound length measurements were conducted from day 0 to day 14. The research data were analyzed statistically using One-Way ANOVA, followed by Duncan's Post Hoc test. The results showed that the most effective group was K45%, , which achieved complete wound healing within 12 days.